Effects of aspirin and statin use on venous thromboembolism prophylaxis and survival in patients with endometrial cancer. Issue 3 (4th March 2022) - Matsuzaki, Shinya; Miller, Heather; Takiuchi, Tsuyoshi; Klar, Maximilian; Matsuo, Koji
ABSTRACT: Introduction: Acetylsalicylic acid (aspirin) and statins are commonly used to manage and prevent cardiovascular diseases. Recent studies have suggested the benefits of aspirin or statin use in venous thromboembolism (VTE) prophylaxis and survival outcome improvement in women with endometrial cancer. Areas covered: In this study, we reviewed the effects of aspirin or statin use on VTE prophylaxis and survival outcome in women with endometrial cancer. Expert opinion: Among women with endometrial cancer, aspirin use exerted a modest effect on VTE prophylaxis, whereas statin use was associated with a decreased prevalence of VTE, especially in women with obesity and type II cancer, compared with those in non-users. Aspirin use improved cause-specific survival in women with endometrial cancer, aged less than 60 years, who were obese and presented with type I cancer. Statin use was associated with better cause-specific survival in women with type II cancer. The combination of aspirin and statins may be the most effective strategy in improving on VTE prophylaxis and survival outcomes in obese women with type II cancer. Targeting of the appropriate population with endometrial cancer may enhance the efficacy of aspirin or statins on VTE prophylaxis and survival outcomes in women with endometrial cancer.